Stimulating the Facial Nerve to Treat Ischemic Stroke: A Systematic Review - Baker, Turner S.; Robeny, Justin; Cruz, Danna; Bruhat, Alexis; Iloreta, Alfred-Marc; Costa, Anthony; Oxley, Thomas James (Frontiers in Neurology, 2021)
Acute ischemic stroke (AIS) is a common devastating disease that has increased yearly in absolute number of cases since 1990.1 While mechanical thrombectomy and tissue plasminogen activator (tPA) have proven to be effective treatments, their window-of-efficacy time is very short, leaving many patients with no viable treatment option. Over recent years there has been a growing interest in stimulating the facial nerves or ganglions to treat AIS. Preclinical studies have consistently demonstrated an increase in collateral blood flow (CBF) following ganglion stimulation, with positive indications in infarct size and neurological scores. Extensive human trials have focused on trans-oral electrical stimulation of the sphenopalatine ganglion, but have suffered from operational limitations and non-significant clinical findings. Regardless, the potential of ganglion stimulation to treat AIS or elongate the window-of-efficacy for current stroke treatments remains extremely promising. This review aims to summarize results from recent trial publications, highlight current innovations, and discuss future directions for the field. Importantly, this review comes after the release of four important clinical trials that were published in mid 2019.